2013
DOI: 10.1182/blood-2012-05-430926
|View full text |Cite
|
Sign up to set email alerts
|

Impact of isolated germline JAK2V617I mutation on human hematopoiesis

Abstract: Key Points• Germline JAK2V617I mutation as a sole genetic event does not suppress hematopoietic stem cells.• JAK2V617I induces weaker constitutive activation than JAK2V617F but considerable cytokine hyperresponsiveness.The association between somatic JAK2 mutation and myeloproliferative neoplasms (MPNs) is now well established. However, because JAK2 mutations are associated with heterogeneous clinical phenotypes and often occur as secondary genetic events, some aspects of JAK2 mutation biology remain to be und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…Recently, familial thrombocytosis has been associated with a germline MPL mutation 37 and a TET2 truncation mutation, 38 but evidence so far has shown that JAK2 mutations, particularly JAK2V 617 F, are acquired independently by individuals. Although 2 recent reports have associated a germline JAK2V 617 I mutation with familial thrombocytosis, 22,23 our study is the first to demonstrate the contribution of a novel germline mutation involving an alternative JAK2 residue to MPN development and to outline the potential mechanisms responsible for causing familial thrombocytosis. We hypothesize that the JAK2R 564 Q mutation prevents apoptosis in hematopoietic stem cells and megakaryocyte progenitors, giving rise to a moderate increase in platelets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, familial thrombocytosis has been associated with a germline MPL mutation 37 and a TET2 truncation mutation, 38 but evidence so far has shown that JAK2 mutations, particularly JAK2V 617 F, are acquired independently by individuals. Although 2 recent reports have associated a germline JAK2V 617 I mutation with familial thrombocytosis, 22,23 our study is the first to demonstrate the contribution of a novel germline mutation involving an alternative JAK2 residue to MPN development and to outline the potential mechanisms responsible for causing familial thrombocytosis. We hypothesize that the JAK2R 564 Q mutation prevents apoptosis in hematopoietic stem cells and megakaryocyte progenitors, giving rise to a moderate increase in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a single other inherited JAK2 mutation has been suggested to be responsible for the development of MPN, 22,23 and this involved an Ile substitution of the well-studied Val 617 residue. Here we describe a novel germline mutation of JAK2 associated with familial ET that does not involve Val 617 but, rather, an alternative residue in the same JH2 domain, Arg 564 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Likewise, 2 germ-line mutations, JAK2 V617I (different from the V617F substitution classically found in 60% of sporadic essential thrombocythemias [ETs]) and JAK2 R564Q (never observed in sporadic MPNs), have been reported. [9][10][11] Several mutations in the TPO gene that lead to increased TPO translation have also been described in families with a thrombocytosis. [12][13][14][15] Here, we report 2 families with hereditary thrombocytosis carrying so far unidentified heterozygous germ-line mutations in JAK2.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Alternatively, the V617I appears to be sufficient to induce a HT phenotype in a qualitatively distinct manner to that of V617F. 8 Identification of the rare HT is also clinically important as an increased risk of thrombotic/hemorrhagic events, splenomegaly, bone marrow fibrosis, and also transformation to acute myeloid leukemia has been noted in previously documented HT kindred. 9,10 Therefore, these recent reports of germline JAK2 mutations in HT compel the incorporation of JAK2 gene analysis, including at least those exons that encode the pseudo-kinase and kinase domains, into the molecular diagnostic algorithm for suspected HT.…”
mentioning
confidence: 99%